2017
DOI: 10.31989/ffhd.v7i7.360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rate of PSA progression and the level of alkaline phosphatase during high dose vitamin C treatment of patients with prostate cancer

Abstract: Citation: Mikirova N., Hunninghake R., Changes in the rate of PSA progression and the level of alkaline phosphatase during high dose vitamin C treatment of patients with prostate cancer. Functional Foods in Health and Disease 2017; 7(7): 511-528 ABSTRACT Introduction: Intravenously administered vitamin C (IVC) may have anti-cancer and antiinflammatory properties. Many studies demonstrated evidence of a good safety profile of IVC treatments and improvement of the quality of life in cancer patients. IVC has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Clinically, retrospective analysis of prostate cancer patients treated with IVC at the Riordan Clinic showed that PSA levels increased more slowly in subjects given more frequent IVC treatments [84].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, retrospective analysis of prostate cancer patients treated with IVC at the Riordan Clinic showed that PSA levels increased more slowly in subjects given more frequent IVC treatments [84].…”
Section: Discussionmentioning
confidence: 99%
“…Increased tumor ascorbate was associated with slowed tumor growth, but alternate day administration of ascorbate resulted in lower tumor inhibition and did not consistently decrease HIF-1 pathway activity compared with daily injections [25]. Our retrospective analysis of prostate cancer patients treated with bolus IVC at the Riordan Clinic (1994-2015) showed that PSA levels increased more slowly in subjects given more frequent IVC treatments [26].…”
Section: Discussionmentioning
confidence: 75%
“…Our retrospective analysis of prostate cancer patients treated with bolus IVC at the Riordan Clinic (1994-2015 showed that PSA levels increased more slowly in subjects given more frequent IVC treatments [24].…”
Section: Discussionmentioning
confidence: 90%